Which example correctly demonstrates polynomial addition

1 answer

To demonstrate polynomial addition, let's take two polynomial examples and show how to add them.

Let: \[ P(x) = 3x^3 + 2x^2 + 5 \] \[ Q(x) = 4x^3 + x + 7 \]

To add these two polynomials, we combine like terms:

  1. First, organize the polynomials by their degree:
    • For \( x^3 \): \( 3x^3 + 4x^3 = 7x^3 \)
    • For \( x^2 \): \( 2x^2 \) (there is no corresponding term in \( Q(x) \))
    • For \( x^1 \): \( 0 + x = x \) (the coefficient of \( x \) in \( P(x) \) is 0)
    • For the constant term: \( 5 + 7 = 12 \)

Putting this together, we have: \[ P(x) + Q(x) = 7x^3 + 2x^2 + x + 12 \]

Thus, the sum of the two polynomials \( P(x) \) and \( Q(x) \) is: \[ 7x^3 + 2x^2 + x + 12 \]

This is a correct demonstration of polynomial addition.

Similar Questions
  1. Which example correctly demonstrates polynomial addition?A, (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B, (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
  2. Which example correctly demonstrates polynomial addition?A) (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B) (2x^2 + 6x +
    1. answers icon 1 answer
  3. Which example correctly demonstrates polynomial addition?A. (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B. (2x^2 + 6x +
    1. answers icon 1 answer
  4. Which example correctly demonstrates polynomial addition?A. (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B. (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
more similar questions